2018
DOI: 10.5551/jat.41095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cardiac Rehabilitation on High-Density Lipoprotein-mediated Cholesterol Efflux Capacity and Paraoxonase-1 Activity in Patients with Acute Coronary Syndrome

Abstract: Aims: We evaluated whether exercised-based cardiac rehabilitation (CR) can ameliorate the HDL function, i.e., cholesterol efflux capacity (CEC) and paraoxonase-1 activity in patients with acute coronary syndrome (ACS).Methods: This study is a retrospective analysis of stored serum from patients with ACS following successful percutaneous coronary intervention. The CEC, measured by a cell-based ex vivo assay using apolipoprotein B-depleted serum and 3H-cholesterol labeled macrophages and arylesterase activity (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
(63 reference statements)
0
13
0
1
Order By: Relevance
“…However, we found no correlation between circulating HDL cholesterol levels and cholesterol efflux capacity in control subjects and ACS patients. Furuyama F et al in their study on effect of cardiac rehabilitation on HDL function have also shown significant correlation of CEC and ARE with apoA-I levels rather than HDL-cholesterol levels [22]. This may be because cholesterol content makes up only about 20% of the HDL particle and even that proportion differs between different HDL particles.…”
Section: Discussionmentioning
confidence: 93%
“…However, we found no correlation between circulating HDL cholesterol levels and cholesterol efflux capacity in control subjects and ACS patients. Furuyama F et al in their study on effect of cardiac rehabilitation on HDL function have also shown significant correlation of CEC and ARE with apoA-I levels rather than HDL-cholesterol levels [22]. This may be because cholesterol content makes up only about 20% of the HDL particle and even that proportion differs between different HDL particles.…”
Section: Discussionmentioning
confidence: 93%
“…However, we found no correlation between circulating HDL cholesterol levels and cholesterol efflux capacity in control subjects and ACS patients. Furuyama F et al in their study on effect of cardiac rehabilitation on HDL function have also shown significant correlation of CEC and ARE with apoA-I levels rather than HDL-cholesterol levels [20]. This may be because cholesterol content makes up only about 20% of the HDL particle and even that proportion differs between different HDL particles.…”
Section: Discussionmentioning
confidence: 93%
“…However, we found no correlation between circulating HDL cholesterol levels and cholesterol efflux capacity in control subjects and ACS patients. Furuyama F et al in their study on effect of cardiac rehabilitation on HDL function have also shown significant correlation of CEC and ARE with apoA-I levels rather than HDLcholesterol levels [22]. This may be because cholesterol content makes up only about 20% of the HDL particle and even that proportion differs between different HDL particles.…”
Section: Discussionmentioning
confidence: 94%